2015
DOI: 10.1103/physrevlett.114.230602
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-Induced Forces in Nonequilibrium Diffusive Dynamics

Abstract: Fluctuations in nonequilibrium steady states generically lead to power law decay of correlations for conserved quantities. Embedded bodies which constrain fluctuations, in turn, experience fluctuation induced forces. We compute these forces for the simple case of parallel slabs in a driven diffusive system. Our model calculations show that the force falls off with slab separation d as k B T=d (at temperature T, and in all spatial dimensions) but can be attractive or repulsive. Unlike the equilibrium Casimir fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 29 publications
(55 reference statements)
1
57
0
Order By: Relevance
“…The solid black curve shows Eq. (22). At low temperatures, the particles are trapped between the two inclusions which become more and more like impenetrable "plates," so that the curve approaches the shape of the curve in Fig.…”
Section: Fluctuation-induced Forcesmentioning
confidence: 92%
See 2 more Smart Citations
“…The solid black curve shows Eq. (22). At low temperatures, the particles are trapped between the two inclusions which become more and more like impenetrable "plates," so that the curve approaches the shape of the curve in Fig.…”
Section: Fluctuation-induced Forcesmentioning
confidence: 92%
“…(22) at high T F as expected, with the only visible deviation for long times, were the simulation data approach zero faster than expected from Eq. (22). The finite size of the simulation box cuts off the power-law decay in time; see Appendix C. In contrast to the 2D case, the PQF is qualitatively different for low T F , where it tends to the result of Sec.…”
Section: B Two Inclusions At Large Separationsmentioning
confidence: 94%
See 1 more Smart Citation
“…negative, essentially depending on whether the concentration dependence of the heat of mixing is convex or concave. Some authors have proposed NE Casimir forces induced by long-range fluctuations that originate from the spatial dependence of the noise correlations associated with the local fluctuation-dissipation theorem in the presence of a gradient [36,37]. However, for fluids it has been found that these NE correlations are insignificant compared to the NE correlations caused by a coupling between hydrodynamic modes in NE states considered here [38].…”
Section: Prl 115 035901 (2015) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Nevertheless, for non-equilibrium systems along with strong correlations, it is uncertain whether scaling arguments could be valid. Recent studies on non-equilibrium systems [188] found that, even under far from equilibrium conditions, unexpected long-range correlations may appear. Power-law behaviors indicate the potential application of scaling analysis; such a treatment, however, has seldom appeared in the literature.…”
Section: Discussionmentioning
confidence: 99%